EFFECT OF MORINGA OLEIFERA LEAF MEAL (MLM) ON SKIN COLOURATION OF ORNAMENTAL GUPPY, POECILIA RETICULATA (PETER, 1860) - MAYANK BISHT; KUMAR, AVDESH; SHAH, TARANG KUMAR; SHARMA, MADHU (Journal of the Inland Fisheries Society of India, 2026)
The present experiment aimed to evaluate the effect of Moringa oleifera leaf meal (MLM) on skin pigmentation of guppies. Two hundred and forty (240) healthy fish were divided into four treatment groups such as control (T0), 5% (MT1), 10% (MT2) and 15% (MT3) MLM in the guppy diet. The concentration of carotenoids in skin increased significantly with increased concentration of MLM in diet. However, the MT3 treatment (15%) had the highest carotenoid concentration. Significant differences were found for redness, yellowness, and whiteness between the treatment groups. A 15% intake of moringa has been found to be suitable to enhance the skin colour and pigmentation of guppies.